LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION OF GREY MULLET, VALAMUGIL SEHELI (FORSKAL), FROM MANGALORE WATERS - Gowda, Gangadhara; Shanbhogue, S L; Udupa, K S (Indian Journal of Fisheries, 2011)
The weight of V. sehell from Mangalore waters increased as an exponential function of its length, and the corresponding’ equation was W = 0.0243L.2-6819 for females and W = 0.407 8L2-5 2 3 4 for males. The fluctuations in the mean Relative condition factor (Kn) suggested that the fish matured for the first time when it attained a length of 240-260 mm.